Two new species from the Mallomonas favosa species complex (Synurales, Chrysophyceae) from acidified water bodies in Vietnam - Ignatenko, Marina E.; Huan, Phan Trong; Gusev, Evgeniy S. (Phytotaxa, 2025)
Two new species of the genus Mallomonas, M. ridens and M. multilobata, are described from acidified water bodies in Vietnam based on silica-scale morphology studied by transmission and scanning electron microscopy. Based on scale ultrastructure, the new species are assigned to the Mallomonas favosa species complex within the section Torquatae. The primary distinguishing feature of both new species is the presence of rounded pits on the shield surface. In M. ridens, the pits are fused into linearly arranged groups of 2–3, exhibiting expansions and constrictions, and are predominantly located along the shield periphery, adjacent to the posterior submarginal rib and the anterior flange. In M. multilobata, the shield possesses numerous rounded pits that are grouped into rosettes of 2–5, with thin partitions separating individual pits. Both species are rare, found in only a few localities.